Pemberian Edukasi PHBS Berbasis Etnosains Di SDN 13 Kubu Gulai Bancah Bukittinggi - Lisa Fradisa; Kalpana Kartika (Universitas Pahlawan Tuanku Tambusai, 2023)
Providing education on Clean and Healthy Behavior (PHBS) based on ethnoscience aims to increase students' knowledge of the importance of self-awareness and the environment by instilling a healthy mindset, through existing local wisdom, relevant to the demands of the times so as to create a healthy, intelligent and cultured school community in facing the era of society 5.0. The lack of knowledge of PHBS in students can lead to various personal and environmental health problems. PHBS is basically all public health behavior carried out on personal awareness. Even though it has long been echoed by the government through the ministry of health, however, PHBS in schools now feels even more crucial considering that face-to-face learning activities have been carried out after the Covid 19 pandemic. They are expected to adopt a healthy lifestyle to create healthy schools and the environment around schools. That way, the teaching and learning process will run smoothly. This activity was carried out at SD Negeri 13 Kubu Gulai Bancah Bukittinggi in the form of counseling with the help of power points, discussions, watching videos and demonstrations of the 6 steps to washing hands properly and correctly. Through this ethnoscience-based PHBS education there was an increase in students' knowledge as evidenced by the great enthusiasm of students and the many questions asked regarding personal health problems and the environment around them. Most students are able to explain and practice how to live a healthy, intelligent and cultured life. Keywords: Education, Ethnoscience, PHBS